The Vitamin D Receptor: New Paradigms for the Regulation of Gene Expression by 1,25-Dihydroxyvitamin D(3) - Pike, J. Wesley (2010)
The actions of the vitamin D hormone 1,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) are mediated by the vitamin D receptor (VDR), a ligand-activated transcription factor that functions to control gene expression. Following ligand activation, the VDR binds directly to specific sequences located near promoters and recruits a variety of coregulatory complexes that perform the additional functions required to modify transcriptional output. Recent advances in transcriptional regulation, which permit the unbiased identification of the regulatory regions of genes, are providing new insight into how genes are regulated. Surprisingly, gene regulation requires the orchestrated efforts of multiple modular enhancers often located many kilobases upstream, downstream or within the transcription units themselves. These studies are transforming our understanding of how 1,25(OH)(2)D(3) regulates gene transcription.